Effect of iron deficiency anemia during pregnancy on T3, T 4 and TSH levels in newborns - Suratmin Suratmin; Siska Mayasari Lubis; Melda Deliana; Hakimi Hakimi (Indonesian Pediatric Society Publishing House, 2011)
Background Iron deficiency anemia (IDA) in infants is associated v.ith maternal iron deficiency anemia during pregnancy. Infants from anemic mothers often have lower hemoglobin levels than those from non􀁐anemic mothers. S everal studies have suggested that IDA in infants can impair thyroid peroxidase (TPO) enzyme which is required to produce thyroid hormones.   Objective To detennine the effects of IDA during pregnancy on T3, T4, and TSH levels in newborns. Methods We conducted a cross􀁐sectional study from September to December 2010 in two hospitals. Mothers' blood specimens were examined for IDA. Newborns' hematocrit, hemoglobin, ferritin, T3, T4, and TSH levels were measured in umbilical vein blood specimens taken at 24 hours of life. Results Mean T3, T4, and TSH levels of 40 newborns whose mothers suffered from IDA were 2.2 nmollL (SD 1.19), 8.4 ug/dL (SD 6.12), and 15.3 mIU/mL (SD 3.99),  respectively. There was no significant relationship between maternal IDA during pregnancy and infant T3 and TSH levels (P=0.96, P=0.29, respectively ). However, maternal IDA significantly correlated 'With infant T4 levels. Conclusion There was no significant relationship between maternal IDA during pregnancy and levels of T3 and TSH in newborns. However, maternal IDA significantly correlated with lower infant T4 levels.